Efektivitas Pengawasan Bawaslu Terhadap Praktik Money Politics di Kota Padang - Tessa Agustina; Mhd Fajri; Aidinil Zetra (Politeia: Jurnal Ilmu Politik, 2026)
This study aims to analyze the effectiveness of the supervision carried out by the General Election Supervisory Agency (Bawaslu) of Padang City in addressing vote-buying practices during the 2024 Local Election. Vote buying remains one of the most pervasive and difficult electoral violations to control, making it necessary to evaluate the extent to which oversight mechanisms can prevent and respond to such practices. This research employs a qualitative approach using a literature study method based on legal documents, official Bawaslu reports, media coverage, and previous scholarly findings. The analysis of effectiveness refers to Mahmudi’s framework, which consists of four components: input, process, output, and outcome. The findings reveal that structurally, Bawaslu Padang has adequate regulatory foundations, human resources, and preventive programs as inputs for the supervision process, although limitations remain in supporting infrastructure and public reporting participation. In the process dimension, Bawaslu conducted vulnerability mapping, public education, campaign monitoring, financial reporting oversight, and case handling. However, the covert and informal-network nature of vote-buying activities made it difficult for supervisors to gather sufficient evidence that meets formal and material requirements. The output of supervision is reflected in the registered reports, field findings, and documented preventive efforts, yet only a few cases could proceed to legal enforcement. The outcome shows that the supervision has not produced a significant deterrent effect nor reduced vote-buying practices at a substantive level.